Digest - Herfarth, Christian; Lehnert, Thomas (The British journal of surgery, 1995)
For this quarter's digest Professor Christian Herfarth and Dr Thomas Lehnert have selected the best from the January to March 1995 issues of Der Chirurg. A digest of the BJS for the same period, written by Professor John Farndon, appears in the German journal.